Turn of the century Paris and Bogota as seen by their painters (19th to 20th century) (2012)
The article analyzes some city paintings about Paris and Bogota done by local artists around the turn of the century, in the late 1800s and early 1900s, taking into account two kinds of urban pictorial representations: i) urban scenes paintings, in which the city is the place for life and so human figures are relevant to the composition; and ii) urban landscape paintings, in which the main character is the city itself and, therefore, portrays of its inhabitants are quite uncommon. From this double point of view, the author examines images of Paris, including, the first dagurreotype as well as works by famous impressionists like Pissarro, Renoir, Van Gogh and Monet; and so it does with the images of Bogota done by two members of the Escuela de la Sabana (Savannah School): Luis Núñez Borda and Fídolo Alfonso González Camargo. Among others, the article concludes that painting is a useful artistic technology for understanding the complexities of the urban experience.